ISOLATION AND IDENTIFICATION OF KLEBSIELLA SP. IN DIARRHEAL KINTAMANI DOG - Putra, Made Deddy Dharmana; Suarjana, I Gusti Ketut; Gelgel, Ketut Tono Pasek (Buletin Veteriner Udayana, 2022)
The Kintamani dog is a germplasm originating from Sukawana Village, Kintamani District, Bangli Regency, Bali Province and has become the fauna mascot of Bangli Regency and for now the Kintamani dog has been recognized as the only dog ??breed from Indonesia that has been recognized worldwide. One of the most common problems in dogs is the occurrence of diseases in the digestive tract, namely diarrhea. Diarrhea that is not treated immediately can have a fatal impact on the affected animal. Klebsiella sp. is a normal bacterial flora in the digestive tract that is an opportunistic pathogen. This study aims to determine or identify Klebsiella sp. in the digestive tract of Kintamani dogs with diarrhea. Klebsiella sp. isolated from rectal swab results in Kintamani dogs with diarrhea and then cultured on EMBA and Sheep Blood Agar media, Gram staining, catalase test, and oxidase test were performed. Then the isolates were identified on Triple Sugar Iron Agar (TSIA), Sulfide Indol Motility (SIM), Simon Citrate Agar (SCA), Methyl Red Voges Proskauer (MRVP), and the Confectionery test. The results showed that from 35 samples, four (11.4%) positive samples of Klebsiella sp. diarrhea in Kintamani dogs. For further research, it is necessary to complement the API 20E test to determine the species of Klebsiella sp. more specific.